2020
DOI: 10.3390/medicina56090457
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Radiological Evaluation of Low-Intensity Pulsed Ultrasound Versus Whole Body Vibration on Healing of Mandibular Bone Defects in Rats

Abstract: Background and Objectives: Mechanical stimulation can improve the structural properties of the fracture site and induce the differentiation of different cell types for bone regeneration. This study aimed to compare the effect of low-intensity pulsed ultrasound stimulation (LIPUS) versus whole body vibration (WBV) on healing of mandibular bone defects. Materials and Methods: A mandibular defect was created in 66 rats. The rats were randomly divided into two groups of rats. Each group was subdivided randomly by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…8 Mechanical stimulation sent by LIPUS can initiate biochemical reactions in cells that promote graft-bone healing and regeneration. 9…”
Section: Discussionmentioning
confidence: 99%
“…8 Mechanical stimulation sent by LIPUS can initiate biochemical reactions in cells that promote graft-bone healing and regeneration. 9…”
Section: Discussionmentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) is a method to mechanically stimulate tissues via ultrasound in the range of 1-4 MHz and 0.01−90 mW/cm 2 . LIPUS was shown to enhance ECM synthesis and regeneration and to be a potent stimulator of osteogenic differentiation and is used, e.g., in the context of fracture healing [327][328][329]. Bone mass and maturation is also increased upon LIPUS treatment in different animal models, and it was shown that osteocytes in particular respond to LIPUS treatment [330,331].…”
Section: May the Force Be With You: Mt And Its Implications For Periodontal Regenerationmentioning
confidence: 99%